2010
DOI: 10.1080/00219266.2010.9656205
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers' attitudes towards and willingness to teach evolution in a changing South African environment

Abstract: This article investigates the attitudes of South African student teachers towards the theory of evolution and their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 12 publications
0
32
0
3
Order By: Relevance
“…Rutledge and Mitchell's study (2002) of 552 practicing secondary biology teachers in Indiana revealed that 67% of participants accepted evolution, with 19% undecided and 14% not accepting. Abrie (2010) found that only 40% of 46 secondary preservice teachers in South Africa accepted evolution, with 12% of teachers designated as uncertain, and 48% being rejecters. Kose (2010) found that 30 of 38 Turkish secondary biology teachers rejected evolution.…”
Section: Nature Of Teachers' Acceptancementioning
confidence: 99%
See 3 more Smart Citations
“…Rutledge and Mitchell's study (2002) of 552 practicing secondary biology teachers in Indiana revealed that 67% of participants accepted evolution, with 19% undecided and 14% not accepting. Abrie (2010) found that only 40% of 46 secondary preservice teachers in South Africa accepted evolution, with 12% of teachers designated as uncertain, and 48% being rejecters. Kose (2010) found that 30 of 38 Turkish secondary biology teachers rejected evolution.…”
Section: Nature Of Teachers' Acceptancementioning
confidence: 99%
“…Acceptance has been measured primarily through multiple choice questionnaires or surveys with Likert-scale responses (Aguillard 1999;Fowler and Meisels 2010;Kose 2010;Losh and Nzekwe 2011a, b;Scharmann 1994;Shankar and Skoog 1993). Many researchers have used items from Rutledge and Warden's (1999) instrument, the Measure of Acceptance of the Theory of Evolution (MATE) (Abrie 2010;Deniz et al 2008;Kim and Nehm 2011;McCrory and Murphy 2009;Rutledge and Warden 2000;Trani 2004). Other methods used to understand teachers' acceptance of evolution have included interviews (Aguillard 1999;Boujaoude et al 2011;Goldston and Kyzer 2009) and concept maps (Rutledge and Mitchell 2002).…”
Section: Summary Of Major Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are four areas of concern: Firstly, teachers' inadequate content knowledge regarding evolution Pillay 2011), probably because many of them had not received appropriate evolution-related education or training prior to the implementation of the new curriculum (Abrie 2010;Pillay 2011;Stears 2006) and because 'training for both Curriculum 2005 and the National Curriculum Statement was shown to be too superficial and too generic' and 'decontextualized and unsupported', resulting in poor implementation of policies (Department of Basic Education 2009:55-56). Secondly, in addition to teachers lacking content knowledge, several studies have found that many South African teachers (Molefe 2013;Naudé 2013;Ngxola and Sanders 2009;Pillay 2011;Yalvac 2011) and student-teachers (Abrie 2010;Stears 2012) have misconceptions about evolution. Thirdly, many teachers (Naudé 2013;Pillay 2011;Sanders 2010;Sanders and Ngxola 2009;Yalvac 2011) and student-teachers (Abrie 2010) have voiced attitude-related concerns (their own, parents', or learners') about a potential religion/evolution controversy, some expressing an unwillingness to teach evolution.…”
Section: Problems Motivating the Studymentioning
confidence: 99%